UNDERSTANDING THE NEXUS OF CLIMATE CHANGE AND URBAN POVERTY: DOMINANT DISCOURSES IN ACADEMIC PUBLICATIONS - Lestari, Dian; Luhur, Andi (Department of Government, FISIP, Universitas Padjadjaran, 2025)
The purpose of this study is to examine recurring themes in publications on the relationship between urban poverty and climate change. CiteSpace and RStudio software are utilised in this study’s bibliometric analysis to retrieve articles from the Scopus database on the relationship between urban poverty and climate change. CiteSpace and RStudio tools were utilised to analyse the data and create visualisations, examining research patterns and topic developments in the areas of urban poverty and climate change governance. The research results identified 13 clusters, with the largest cluster being